2009
DOI: 10.2217/nnm.09.61
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Nanoparticles and Platelet Reactivity

Abstract: Aim-Nanosized particles (NPs) enriched in hydroxyapatite and protein isolated from calcified human tissue accelerate occlusion of endothelium-denuded arteries when injected intravenously into rabbits. Since platelet aggregation and secretory processes participate in normal hemostasis, thrombosis and vascular remodeling, experiments were designed to determine if these biologic NPs alter specific platelet functions in vitro.Methods-Platelet-rich plasma was prepared from citrate anticoagulated human blood. Platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Previous studies suggested that natural hydroxyapatite particles from human calcified tissue may interfere with platelet aggregation [30][31][32]. In the present study it was shown that doped and nondoped HAP nanoparticles did not interfere with the coagulation pathway up to a concentration of 250 mg/mL.…”
Section: Platelet Adhesion and Activationsupporting
confidence: 52%
“…Previous studies suggested that natural hydroxyapatite particles from human calcified tissue may interfere with platelet aggregation [30][31][32]. In the present study it was shown that doped and nondoped HAP nanoparticles did not interfere with the coagulation pathway up to a concentration of 250 mg/mL.…”
Section: Platelet Adhesion and Activationsupporting
confidence: 52%
“…For instance, multi walled carbon nanotubes (MWNT) and single walled carbon nanotubes (SWNT) induce platelet aggregation, but not activation [58]. Contrary to that, biological NPs (hydroxyapetite-HA and calcified NP) inhibited platelet aggregation but induced activation [59]. A similar observation was made for TiO 2 NPs [60].…”
Section: Thrombocytes/plateletsmentioning
confidence: 62%
“…Women randomized to active treatments also received oral progesterone (Prometrium; micronized progesterone, 200 mg/day) for 12 days each month for the duration of the study to protect the uterus. Each participant underwent a medical examination, including body morphometrics and standard blood chemistries prior to randomization 19, 22 .…”
Section: Methodsmentioning
confidence: 99%